Causes of Mobile Phone Addiction - Yuwanto, Listyo (Faculty of Psychology, Universitas Surabaya, 2010)
The technology of mobile phones (MP) has made fast advances. Cellular phone addiction has been discussed widely. Many researchers explored the causes of cellular phone addiction. The purpose of this study was to describe and analyze the possible factors causing mobile phone addiction. Data was gathered through literature studies. Results show four factors causing mobile phone addiction; namely internal and external factors, social, and situational factor. Results of the study were discussed further. Teknologi telepon genggam mengalami kemajuan yang sangat pesat. Kecanduan telepon genggam telah didiskusikan secara luas tahun-tahun terakhir. Banyak penelitian mengeksplorasi penyebab kecanduan telepon genggam. Data dikumpulkan melalui studi literatur dan survey interviews pada 30 responden yang mengalami kecanduan telepon genggam. Hasil penelitian menunjukkan terdapat 4 faktor penyebab kecanduan telepon genggam yaitu faktor internal, eksternal, sosial, dan situasional. Hasil penelitian didiskusikan lebih lanjut.